Microscopic Changes of the Placental Components in Maternal Anaemia (Bangladesh Journal of Anatomy, 2011)
Background: The placenta is vital for the maintenance of a normal pregnancy. Foetal growth and wellbeing depend on the functional and structural component of the placenta. The architecture of the placenta has been claimed to be changed in maternal diseases like anaemia. Study design: Descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka, from July 2005 to June 2006Materials and Methods: Sixty (60) placentae of Bangladeshi women were collected from Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital and Maternal and Child Health Training Institute (widely known as Azimpur Maternity), Dhaka within 6 hours of delivery. Out of 60 placentae, anaemic and control group were 40 and 20 respectively. The study was designed to determine the histological changes of placental components, which is influenced by maternal anaemia. Microscopic study of placenta was done by light compound microscope with Harris’ Haematoxylin & Eosin stain. The samples were divided into group A (control), group B1 (mild anaemia), group B2 (moderate anaemia) and group B3 (severe anaemia). Result: Pathological areas were significantly increased and villous area was reduced in anaemic groups. Conclusion: A comprehensive work considering the physiological, biochemical, genetic, electron microscopic and morphometric placental studies are needed to support the present study. Keywords: Maternal anaemia; placenta; villous area; pathological area. DOI: 10.3329/bja.v8i2.7017Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 59-63